2006
DOI: 10.1016/j.febslet.2006.04.094
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of leptin signalling in hematopoietic cells using an adapted MAPPIT strategy

Abstract: The adipocyte-secreted hormone leptin participates in the regulation of hematopoiesis and enhances proliferation of hematopoietic cells. We used an adaptation of the MAPPIT mammalian two-hybrid method to study leptin signalling in a hematopoietic setting. We confirmed the known interactions of suppressor of cytokine signalling 3 (SOCS3) and STAT5 with the Y985 and Y1077 motifs of the leptin receptor, respectively. We also provide evidence for novel interactions at the Y1077 motif, including phospholipase C gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…9 Phosphorylation of Tyr985 also promotes recruitment of SHP2 for activation of extracellular signalYregulated kinase as well as attenuation of RasGTPase-p62Dok, leading to stimulation of Ras activity and cell proliferation. 23 Tyr1077 phosphorylation of Ob-Rb induces activation of STAT5, resulting in peroxisome proliferatorY activated receptor F overexpression 23 Previously, Pallares et al 24 that found NF-JB family may be important in endometrial carcinogenesis, by controlling apoptosis and cell proliferation after they detected NF-JB family and IJB families expression in human EC. In our experiments, leptin induced NIK/IKK phosphorylation and subsequent NF-JB activation, leading to inhibition of EC cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…9 Phosphorylation of Tyr985 also promotes recruitment of SHP2 for activation of extracellular signalYregulated kinase as well as attenuation of RasGTPase-p62Dok, leading to stimulation of Ras activity and cell proliferation. 23 Tyr1077 phosphorylation of Ob-Rb induces activation of STAT5, resulting in peroxisome proliferatorY activated receptor F overexpression 23 Previously, Pallares et al 24 that found NF-JB family may be important in endometrial carcinogenesis, by controlling apoptosis and cell proliferation after they detected NF-JB family and IJB families expression in human EC. In our experiments, leptin induced NIK/IKK phosphorylation and subsequent NF-JB activation, leading to inhibition of EC cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…SOCS2 can impair the inhibitory effect of SOCS1 or SOCS3 on leptin-induced signalling (69), and it can interfere with the association of CIS to the OB-R membrane proximal tyrosine (70). Also SOCS6 and SOCS7 can interact with the OB-R. SOCS7 may be implicated in OB-R signalling termination (71), i.e. by inhibiting STAT3 activation and/or by interacting with activated STAT3 to prevent translocation to the nucleus (72).…”
Section: Suppressors Of Cytokine Signalling (Socs)mentioning
confidence: 99%
“…Using the βc setup ( Figure 1F), we confirmed the binding of CIS, SOCS2 and STAT5a to the Tyr-1077 motif in the murine Ba/F3 pro-B cell line and revealed that, in addition, PLCγ , SOCS6 and SOCS7 also interact with the Tyr-1077 motif [8]. More recently, MAPPIT experiments in both HEK-293T and in the physiologically highly relevant N38 hypothalamic cell line revealed that IRS4 (insulin receptor substrate 4) interacts with the Tyr-1077 motif.…”
Section: Lrmentioning
confidence: 64%
“…To be able to use MAPPIT in haemopoietic cells that have no or very low STAT3 levels, βc (beta common) MAPPIT was created, which employs STAT5 as a signal transducer. To accomplice this, the prey was fused to a portion of the βc chain containing STAT5 recruitment sites ( Figure 1F) [8].…”
Section: Mappit (Mammalian Protein-protein Interaction Trap)mentioning
confidence: 99%